2010
DOI: 10.1165/rcmb.2009-0155oc
|View full text |Cite
|
Sign up to set email alerts
|

17,18-Epoxyeicosatetraenoic Acid Targets PPARγ and p38 Mitogen–Activated Protein Kinase to Mediate Its Anti-inflammatory Effects in the Lung

Abstract: This study sought to assess putative pathways involved in the anti-inflammatory effects of 17,18-epoxyeicosatetraenoic acid (17,18-EpETE), as measured by a decrease in the contractile reactivity and Ca(2+) sensitivity of TNF-α-pretreated human bronchi. Tension measurements performed in the presence of 12-(3-adamantan-1-yl-ureido)-dodecanoic acid (AUDA), a soluble epoxide hydrolase (sEH)-specific inhibitor, demonstrated that 17,18-EpETE reduced the reactivity of TNF-α-pretreated tissues. The overexpression of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 44 publications
3
105
0
1
Order By: Relevance
“…A recent study revealed that 17,18-EEQ is also a potent regulator of human lung inflammation, and it remains to be seen whether this EPA metabolite may provide protection against critical inflammatory bronchial disorders (76). In the brain, EETs are involved in neurovascular signaling (77) and neuroprotection (78).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that 17,18-EEQ is also a potent regulator of human lung inflammation, and it remains to be seen whether this EPA metabolite may provide protection against critical inflammatory bronchial disorders (76). In the brain, EETs are involved in neurovascular signaling (77) and neuroprotection (78).…”
Section: Discussionmentioning
confidence: 99%
“…The epoxy-metabolites of all three PUFAs share vasodilatory properties, whereby the potencies of EEQs and EDPs may largely exceed those of EETs in some vascular beds ( 18,25 ). Anti-infl ammatory effects were fi rst revealed for 11,12-and 14,15-EET but are also exerted by EPA-epoxides, as exemplifi ed by 17,18-EEQ ( 26,27 -and isoproterenol-induced increased contractility of neonatal cardiomyocytes, indicating that these metabolites may act as endogenous antiarrhythmic agents ( 22 ). Whereas certain EET regioisomers promote tumor angiogenesis and metastasis, 19,20-EDP and other regioisomeric DHA-epoxides inhibit these crucial events in cancerogenesis ( 28,29 ).…”
Section: Determination Of Eicosanoid Profi Lesmentioning
confidence: 99%
“…Relationship between LXA 4 Levels and sEH Activity sEH expression is increased by oxidative stress (21), abundant in asthmatic airways (22), and its activity can influence LX generation by human cells in vitro and in rodent lung in vivo (18, 23), so we next determined if there was a relationship between LXA 4 levels and sEH activity in the sputum supernatants from subjects with asthma ( Figure 3). Because 14,15-EET is a prominent cytochrome P-450-derived eicosanoid in the lung that is converted by sEH to 14,15-DHET (24), the product/ precursor ratio of 14,15-DHET to 14,15-EET was used as an index for sEH activity.…”
Section: Lxa 4 Generation Is Inversely Related To Oxidative Stress Inmentioning
confidence: 99%